2012
DOI: 10.1016/j.orl.2012.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Complexity results for the gap inequalities for the max-cut problem

Abstract: In 1996, Laurent and Poljak introduced an extremely general class of cutting planes for the max-cut problem, called gap inequalities. We prove several results about them, including the following: (i) there must exist non-dominated gap inequalities with gap larger than 1, unless = co-; (ii) there must exist non-dominated gap inequalities with exponentially large coefficients, unless = co-; (iii) the separation problem for gap inequalities can be solved in finite time (specifically, doubly exponential time).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…For example, from a consideration of 3-by-3 principal submatrices of Z, it can be shown that a point in the projection cannot violate any of the triangle inequalities (10), (11) by more than 1/4. This provides a partial explanation for the strength of the SDP bound; see, e.g., [8,29,57,58] for more details.…”
Section: Now We Introduce the Matrixmentioning
confidence: 98%
“…For example, from a consideration of 3-by-3 principal submatrices of Z, it can be shown that a point in the projection cannot violate any of the triangle inequalities (10), (11) by more than 1/4. This provides a partial explanation for the strength of the SDP bound; see, e.g., [8,29,57,58] for more details.…”
Section: Now We Introduce the Matrixmentioning
confidence: 98%